Changes in the structural features of osteoarthritis in a year of weight loss - Jafarzadeh, S. Reza (Osteoarthritis Cartilage, 2018)
OBJECTIVE: In patients undergoing bariatric surgery or medical management for obesity, we assessed whether those experiencing substantial weight loss had changes in innervated knee structures or in cartilage. METHODS: Severely obese patients (BMI ≥35) with knee pain on most days were seen before bariatric surgery or medical weight management and at 1-year follow-up. Examinations included 3T MRI acquired at both time points for semi-quantitative scoring of bone marrow lesions (BML), synovitis, cartilage damage, and for quantitative measurement of cartilage thickness. Association of ≥20% vs. <20% weight loss with change in semi-quantitative scores was evaluated using linear mixed-effects models, and that with cartilage thickness change used non-parametric and parametric methods. Sensitivity analyses tested different thresholds for weight loss, weight loss as a continuous measure, examined those with and without bariatric surgery, and with worse osteoarthritis (OA). RESULTS: 75 subjects (median age 49 years, 92% women) were included. At baseline, 61 subjects (81%) had Kellgren and Lawrence (KL) grade >0, and 16 (21%) had KL grade ≥3; 69 (92%) had cartilage damage. For BML, synovitis, and cartilage damage, the majority of knees had change in semi-quantitative scores of 0, and there was no difference between those with and without ≥20% weight loss. Similarly, in terms of cartilage thickness loss, in 14 of 16 sub-regions thickness loss was not associated with weight loss. Sensitivity analyses showed similar findings. CONCLUSION: In middle-aged persons with mostly mild radiographic OA, structural features changed little over a year and weight loss was not associated with effects on structural changes.